Right heart structural changes are independently associated with exercise capacity in non-severe COPD. - Michael J Cuttica; Sanjiv J Shah; Sharon R Rosenberg; Randy Orr; Lauren Beussink; Jane E Dematte; Lewis J Smith; Ravi Kalhan (PLoS ONE, 2011)
Pulmonary hypertension (PH) occurs frequently and results in functional limitation in advanced COPD. Data regarding the functional consequence of PH in less severe COPD are limited. Whether echocardiographic evidence of right sided heart pathology is associated with functional outcomes in patients with non-severe COPD is unknown.We evaluated pulmonary function, six minute walk distance, and echocardiography in 74 consecutive patients with non-severe COPD. We performed multivariable linear regression to evaluate the association between right heart echocardiographic parameters and six minute walk distance adjusting for lung function, age, sex, race, and BMI.The mean six minute walk distance was 324±106 meters. All subjects had preserved left ventricular (LV) systolic function (LV ejection fraction 62.3%±6.1%). 54.1% had evidence of some degree of diastolic dysfunction. 17.6% of subjects had evidence of right ventricular enlargement and 36.5% had right atrial enlargement. In univariate analysis RV wall thickness (β = -68.6; p = 0.002), log right atrial area (β = -297.9; p = 0.004), LV mass index (β = -1.3; p = 0.03), E/E' ratio (β = -5.5; p = 0.02), and degree of diastolic dysfunction (β = -42.8; p = 0.006) were associated with six minute walk distance. After adjustment for co-variables, the associations between right atrial area (log right atrial area β = -349.8; p = 0.003) and right ventricular wall thickness (β = -43.8; p = 0.04) with lower six minute walk distance remained significant independent of forced expiratory volume in one second (FEV1). LV mass index, E/E' ratio, and degree of diastolic dysfunction were not independent predictors of six minute walk distance.In patients with non-severe COPD right sided cardiac structural changes are associated with lower six minute walk distance independent of lung function. These findings may indicate that echocardiographic evidence of pulmonary hypertension is present in patients with non-severe COPD and has important functional consequences.